The mediating effect of somatic symptom disorder between psychological factors and quality of life among Chinese breast cancer patients - Li, Zimeng; Zhang, Yening; Pang, Ying; He, Yi; Song, Lili; Wang, Yan; He, Shuangzhi; Tang, Lili (Frontiers in Psychiatry, 2023)
Objective We conducted this cross-sectional study to explore the mediating and predicting role of somatic symptom disorder (SSD) between psychological measures and quality of life (QOL) in Chinese breast cancer patients. Methods Breast cancer patients were recruited from three clinics in Beijing. Screening tools included: the Patient Health Questionnaire-15 (PHQ-15), the Patient Health Questionnaire-9 (PHQ-9), the General Anxiety Disorder-7 (GAD-7), the Health Anxiety Scale (Whiteley index-8, WI-8), the Somatic Symptom Disorder B-Criteria Scale (SSD-12), the Fear of Cancer Recurrence (FCR-4), the Brief Illness Perception Questionnaire (BIPQ-8), and the Functional Assessment of Cancer Therapy-Breast (FACT-B). Chi-square tests, nonparametric tests, mediating effect analysis and linear regression analysis were used for the data analysis. Results Among the 264 participants, 25.0% of the patients were screened positive for SSD. The patients with screened positive SSD had a lower performance status and more patients with screened positive SSD received Traditional Chinese Medicine (TCM) (P<0.05). Strong mediating effects of SSD were found between psychological measures and QOL in patients with breast cancer after adjusting sociodemographic variables as covariates (P<0.001). The rang of the percentage mediating effects were 25.67% (independent variable=PHQ-9) to 34.68% (independent variable=WI-8). The SSD predicted low QOL on physical (B=-0.476, P<0.001), social (B=-0.163, P<0.001), emotional (B=-0.304, P<0.001) and functional (B=-0.283, P<0.001) well-being, as well as significant concerns caused by breast cancer (B=-0.354, P<0.001). Conclusions Screened positive SSD had strong mediating effects between psychological factors and quality of life in breast cancer patients. Additionally, screened positive SSD was a significant predictor of lower QOL in breast cancer patients. Effective psychosocial intervention for improving QOL should consider preventing and treating SSD or integrated SSD caring dimensions for breast cancer patients.